KOMPETENSI STRATEGIS MATEMATIS PESERTA DIDIK KELAS XI SMK PADA MATERI SISTEM PERSAMAAN LINIER TIGA VARIABEL - Ikhsan Baihaqi; Kiki Nia Sania Effendi (IKIP Siliwangi, 2023)
The purpose of this study is to describe the mathematical strategic competence of students at the Vocational High School (VHS) level on the material of the Three Variable Linear Equation System (TVLES). The type of research used is descriptive qualitative research. The research subjects were 12 students from class XI AK in one of the vocational schools in Karawang Regency. Methods of data collection using a test instrument. The data was processed with descriptive statistics to determine the high, medium, low criteria of the 12 students. Based on the results of the analysis, the average value of the subject's data is 66.67, which is still below the Minimum Completeness Criteria (KKM) for mathematics at the school. From the results obtained, the researcher describes that students with high strategic competence abilities are able to fulfill the three indicators, namely formulating, representing, and solving problems, students with moderate strategic competencies tend to be better at representing indicators, and subjects with moderate abilities. low has low achievement on each indicator